Apple Incorporated : European Commission Fines for Tax Evasion (B) - Edwards, Jordan W.; Desai, Aniket Naik; Oduro, Abigail; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2017)
The case outlines Tim Cook's reaction to the EU's decision that Apple had received special treatment in terms of its taxation in Ireland and the order to pay 13 billion euros plus interest in tax.
Originally published in Edwards, J., Desai, A., Oduro, A. & O'Rourke, J. (2017). Apple Incorporated: European Commission fines for tax evasion (B). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Apple Computer, Inc. -- Case studies; License agreements -- Taxation -- Law and legislation -- European Union countries -- Case studies; Corporations -- Taxation -- Law and legislation -- European Union countries -- Case studies